Case report on the marathon preparation of two middle-aged women aiming for a 4-hour finish - Zając, Bartosz; Mika, Anna; Szablewska, Anna Weronika (Frontiers in Physiology, 2026)
BackgroundRecreational marathoners targeting the 4-h benchmark are underrepresented in the literature compared with elite runners, despite constituting a substantial share of participants. This case report documents the multifactorial, real-world preparation undertaken by two eumenorrheic middle-aged women and examines how training load, nutritional education, changes in body mass and composition, race-day weather conditions, and pacing strategy collectively contributed to an ∼20% improvement in performance.MethodsThe retrospective analysis included training records from the 26 weeks preceding the marathon, outcomes of the Field-Based Running Test (lactate threshold velocity, mean velocity during the 5-min All-Out Trial, and maximal velocity), changes in body mass and composition, nutritional recommendations, race-day weather conditions, pacing strategy, and self-reported gastrointestinal symptoms.ResultsWeekly running volume ranged 46–65 km, with a predominant frequency of four sessions per week. Both women completed two long runs ≥30 km during the final 4 weeks prior to the race. When classified relative to target marathon velocity, their intensity distributions appeared similar; however, the Field-Test–anchored system revealed clear differences: Woman A accumulated substantially more work in Zones 3–6, whereas Woman B trained proportionally more in Zones 1–2. Both athletes reduced body mass primarily through fat loss, but Woman A registered nearly twice the percentage decrease in absolute body mass and fat mass, and additionally showed a marked decline in muscle mass, accounting for roughly one-third of the total reduction. Both athletes improved their marathon performance by approximately 20%. Positive split pacing strategy observed in both cases. Neither athlete reported gastrointestinal problems during the marathon, held in 0.0 °C–2.2 °C air temperatures with wind speeds of 1.6–7.1 m s–1.ConclusionThis study demonstrates that a combination of prescribed training load, nutritional education, body mass reduction primarily through fat mass loss, as well as optimized pacing strategy can substantially improve marathon performance in middle-age women targeting a ∼4-h finish. Despite experiencing health issues in the final weeks of preparation, both participants achieved meaningful progress, underscoring the practical value of an integrated approach. Although not generalizable, these insights may assist coaches and athletes in designing effective preparation strategies for similar goals.